Resource Based Business Resilience The Moderating Role Of Akhlakul Karimah In The Ar Rahman Human Being Model - Abdurrahman Achmad (Economics and Business Journal (ECBIS), 2026)
This study examines the Ar Rahman Human Being (ARHB) Model as an integrative framework of resource-based business resilience by incorporating akhlakul karimah as moral capital functioning as an internal governance mechanism. The study addresses the limitation of the resource-based view (RBV), which tends to emphasize resource capacity without adequately considering the normative dimension guiding its utilization. A contingency model is proposed that positions internal moral quality as a conditioning factor for the effectiveness of strategic resources in enhancing business resilience. Using an explanatory quantitative approach with a cross-sectional design, data were collected from 250 micro and small enterprise (MSE) owners in Makassar City. Structural Equation Modeling based on Partial Least Squares (SEM-PLS) was employed to analyze the direct effects of expertise, education and training, physical capacity, and capital on business resilience, as well as the moderating role of akhlakul karimah in these relationships. The results indicate that expertise, education and training, physical capacity, and capital positively influence business resilience. Furthermore, akhlakul karimah strengthens the relationship between strategic resources and business resilience, suggesting that the effectiveness of transforming technical capacities into business resilience is contingent upon the entrepreneur’s internal moral quality. These findings extend resource-based business resilience discourse by integrating moral capital as an internal governance mechanism.